Analysis of the Influence of Pit Unit Arrangement on the Drag Reduction Performance of Fish-scale Pits. Issue 2 (April 2021) - Hou, Jin-Ming; Shi, Guang-Feng; Li, Liang; Li, hong-Da; Xia, mingqiang
Abstract: Apply Computational Fluid Dynamics (CFD) method to calculate the drag reduction effect of fish-scale pits with different arrangements under the same conditions. Through the analysis of wall shear stress, wall turbulence energy and axial velocity cloud diagram and velocity vector. It was found that the fish-scale pits can effectively reduce the shear stress and turbulent flow energy on the wall. At the same time, it was found that the bottom of the fish-scale pits formed tiny vortices flowing in the opposite direction. The "vortex cushion effect" is combined with the "pushing effect" caused by the friction generated by the bottom vortex, thereby reducing the friction. The research results show that the rhombus arrangement 2 can arrange a denser pit unit in the effective area to achieve a better drag reduction effect, and its drag reduction rate reaches 6.05%.